إتجاهات الشباب الجاهع نحو تأثير إنستغرام على القين الأخلاقية - أحمودة, طارق; بالعروسي, صلاح الدين (جامعة الوادي - University of Eloued, 2022)
This study came about the university youth’s attitudes towards the influence of Instagram on moral values, and the study problem focused on answering the following questions: _ What are the attitudes of university youth towards the influence of Instagram on moral values? From this, the following sub-questions were raised: What are the habits and patterns of university youth use of the Instagram application? What kind of videos are posted on Instagram? Through our analysis of the partial questions of the study, it became clear that: Existence of the habits and patterns of university students' use of Instagram. There is a type of videos that are published on Instagram, which is social and cultural videos. There are trends for university youth towards the impact of Instagram on moral values
دراسة هيدانية لعينة هن طلبة جاهعة الوادي
مذكرة ماستر إعلام وإتصال
Keywords: trends - youth - Instagram